2017
DOI: 10.2147/dddt.s124273
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrolysin for functional recovery in patients with acute ischemic stroke: a meta-analysis of randomized controlled trials

Abstract: Cerebrolysin has been shown to have an inconsistent efficacy on functional recovery in patients with acute ischemic stroke (AIS). The present meta-analysis aims to evaluate the value of cerebrolysin and to explore the potential influencing factors. The main electronic databases, including MEDLINE, EMBASE, and the Cochrane Library, were searched. The primary outcome was functional recovery at Day 90. The secondary outcomes included mortality and adverse events. A total of 1,649 patients with AIS were pooled fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 34 publications
0
21
0
1
Order By: Relevance
“…Another recent meta-analysis resulting in “no significant efficacy on the neurological functional recovery” was based on dichotomization of mRS, NIHSS, and BI at day 90, i.e., not on full outcome scales [ 36 ]. As highlighted by leading researchers and methodologists, dichotomization of a full scale is burdened with loss of power and arbitrary choice of cutoffs [ 22 , 37 , 38 ], allowing only limited statements on treatment effects.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent meta-analysis resulting in “no significant efficacy on the neurological functional recovery” was based on dichotomization of mRS, NIHSS, and BI at day 90, i.e., not on full outcome scales [ 36 ]. As highlighted by leading researchers and methodologists, dichotomization of a full scale is burdened with loss of power and arbitrary choice of cutoffs [ 22 , 37 , 38 ], allowing only limited statements on treatment effects.…”
Section: Discussionmentioning
confidence: 99%
“…Показана клиническая эффективность препарата церебролизин (Ц) в комплексной терапии неврологических [18,19] и нейродегенеративных заболеваний, включая БА и MCI [20][21][22]. Ц содержит аминокислоты (85%) и пептиды (15%) нейротрофинов, энкефалинов, орексина, галанина, нейротрансмиттеров.…”
unclassified
“…To date five meta-analyses of RCTs investigating the efficacy of Cerebrolysin in acute ischemic stroke have been performed [ 38 42 ]. Three, evaluating aggregate data from up to seven trials involving 1501 to 1779 patients, concluded that the medication did not demonstrate any clinical benefit [ 38 , 41 , 42 ]. In particular, a Cochrane Review did not find Cerebrolysin to be useful, but several trials were excluded from the analysis since treatment initiation exceeded the review protocol’s prespecified 48-h stroke-onset window [ 38 ].…”
Section: Discussionmentioning
confidence: 99%